Measurement of Internal Friction for Tungsten by the Curve Vibrating Method with Variation of Voltage and Temperature - Elin Yusibani; Kosuke Yoshimura; Kanei Shinzato (Journal of Aceh Physics Society, 2013)
Application of a curved vibrating wire method (CVM) to measure gas viscosity has been widely used. A ﬁne Tungsten wire with 50 mm of diameter is bent into a semi-circular shape and arranged symmetrically in a magnetic ﬁeld of about 0.2 T. The frequency domain is used for calculating the viscosity as a response for forced oscillation of the wire. Internal friction is one of the parameter in the CVM which is has to be measured beforeahead. Internal friction coefﬁcien for the wire material which is the inverse of the quality factor has to be measured in a vacuum condition. The term involving internal friction actually represents the effective resistance of motion due to all non-viscous damping phenomena including internal friction and magnetic damping. The testing of internal friction measurement shows that at different induced voltage and elevated temperature at a vacuum condition, it gives the value of internal friction for Tungsten is around 1 to 4 10-4.